THE SOCIAL AND RECREATIONAL LIFESTYLES OF THE ELDERLY IN KWARA STATE, NIGERIA - Orire, Ismaila Oloyede (FUDMA JOURNAL OF SCIENCES, 2020)
Our world is rapidly ageing. A process which exposes individuals to increasing risk of illness and disability of which quality lifestyle is crucial for promoting desired well-being and longevity. Certain objectives were examined, which are to: assess the socio-demographic structure of respondents; determine the social and, recreational lifestyles of the respondents; and determine the common/regularity of participation in socio-recreational activities in the state. Primary and secondary data were used. A multi-stage sampling technique was employed to sample 488 elderly respondents, from six of the 16 LGAs of Kwara State using copies of structured questionnaire. Thus, the result shows that majority of respondents (88%) are between ‘young old’ (60-74) age category. About 36% of respondents were with either primary, secondary or tertiary level education, while 30.1% had acquired only the quranic education. Praying and other religious activities are the major (41%) social activity engaged in, while 32.8% are engaged into farming and other commercial activities. Birthday events are the least attended function by respondents. Also, 38.5% see visitation to friends and relations as major recreational activity, while daily and weekly sporting exercises are engaged in by 40.5% and 42.9% of respondents respectively. The study recommends the establishment of modern and affordable recreational centers for the elderly in the state, encourage optimum utilization and overall enhancement of their health and wellbeing. Hence, appropriate policies and programmes to ensure their equal access to health care, basic social services and social safety nets to protect them from falling into poverty is essential and overdue.